What goes around, comes around: Effects of offshore outsourcing on the export performance of firms - Bertrand, Olivier (Journal of International Business Studies, 2011)
We examine the effect of offshore outsourcing on the export performance of firms. Building on the theories of international business, the resource-based view and transaction cost economics, we argue that offshore outsourcing helps firms – directly or indirectly – to export more. It may reduce their production costs and enhance their flexibility. It may also provide them with new resources and market knowledge. However, the impact of offshore outsourcing depends on the resources and capabilities of firms to manage a network of foreign suppliers, and to absorb foreign knowledge. Using a database of around 2000 manufacturing MNEs in France in 1999, we find that offshore outsourcing increases export performance, the effects being stronger in the export markets where firms import intermediate goods. We also show that the firm size, the organization of intra-firm imports and the export experience moderate the effects of offshore outsourcing positively. These findings have implications for firms and policymakers.